Чудеса, да и только: [сказки] / Наталья Абрамцева - Абрамцева Наталья Корнельевна (Сказка за сказкой, 2017)
Экземпляры: ф.6 (2019) / Инвентарный номер: 55326 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: A16 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6